Morphological and molecular characterization of Desmicola ryukyuensis n. sp. (Nematoda: Oxyuridomorpha: Thelastomatidae) from the wood-feeding cockroach Panesthia angustipennis yayeyamensis Asahina, 1988 (Blattaria: Blaberidae) in the Ryukyu Archipelago, Japan - Morffe, Jans; García, Nayla; Hasegawa, Koichi (Zootaxa, 2023)
Desmicola ryukyuensis n. sp. (Nematoda: Oxyuridomorpha: Thelastomatidae) is described from the wood-feeding cockroach Panesthia angustipennis yayeyamensis Asahina, 1988 (Blattaria: Blaberidae) in Iriomote Island, Japan. The males of D. ryukyuensis n. sp. are similar to D. lamdongensis Sokolova, 2019 but differ by the length of the spicule and the extension of the lateral alae. The females of D. ryukyuensis n. sp. resemble those of D. ornata Jex, Schneider, Rose & Cribb, 2005, but can be differentiated by the shape of the sensilla in the interlabial space and the presence of lateral alae in D. ryukyuensis n. sp. that are absent in D. ornata. The females of D. ryukyuensis n. sp. are similar to D. lamdongensis. However, they differ in the morphology of the lips and the size of the eggs. The phylogeny of D. ryukyuensis n. sp. is inferred by the D2-D3 domains of the 28S rDNA. The new species forms a clade with another sequence of an unidentified Desmicola species from a Vietnamese wood-feeding cockroach.